Risk stratified follow up for head and neck cancer patients – An evidence based proposal. (August 2021) - De Felice, Francesca; Lei, Mary; Oakley, Richard; Lyons, Andrew; Fry, Alastair; Jeannon, Jean-Pierre; Simo, Ricard; Guerrero Urbano, Teresa
Highlights: Head & neck squamous cell cancer (HNSCC) requires a multidisciplinary team approach. Diagnosis and treatment can significantly impact on patients' quality of life. Follow up is crucial to detect recurrence, manage toxicity and address patient needs. We propose a risk stratified follow up protocol for HNSCC patients. Abstract: Head and neck squamous cell carcinoma (HNSCC) has a significant impact on patients' quality of life and treatment can be associated with severe morbidity. Following completion of treatment, patients are followed up in order to detect potentially salvageable recurrences and to manage long-term toxicities. In recent years, a growing interest has been given to risk stratified follow-up interventions to prevent and detect recurrences and manage treatment toxicities in other tumour sites as well as to transfer some of that care to community services. We review the literature for HNSCC and propose a risk stratified follow up protocol to address these issues and assist clinicians in decision making. A shift in patterns of care is suggested in order to provide a basis to improve care for HNSCC patients after complete response to primary treatment.